ダイ 29 ジ ナンキョク チイキ カンソク タイ セールロンダーネ サンチ シュウヘン ニ オケル インセキ タンサ ホウコク 1988-1989 - 奈良岡, 浩; ナラオカ, ヒロシ; 矢内, 桂三; ヤナイ, ケイゾウ; 藤田, 秀二; フジタ, シュウジ; Naraoka, Hiroshi; Yanai, Keizo; Fujita, Shuji (1990)
P(論文) 第29次南極地域観測隊のあすか越冬隊は, セールロンダーネ山地周辺の裸氷域において1988年1月から1989年1月までの間に5回にわたる隕石探査を実施した。その結果, 主に3つの裸氷域から約2000個の隕石を発見, 採集した。総重量はおそらく400kgを越えるであろう。これらの隕石はAsuka-88およびAsuka-89隕石と命名される予定である。予備的な分類によると普通コンドライトが最も多く, 隕鉄や石鉄隕石, エコンドライト, 炭素質コンドライトおよび珍しい種類の隕石も含まれている。今回採集した最大の隕石は46kgのLLタイプのコンドライトである。 A systematic search for Antarctic meteorites was carried out by the Asuka winter party of the 29th Japanese Antarctic Research Expedition on the bare ice field around the Sør Rondane Mountains in the 1987-1988 and 1988-1989 field seasons. More than 2000 meteorite specimens as individuals or fragments were collected from three main areas around the mountains. Their total weight could be more than 400kg. The collection of these meteorites, which will be named officially Asuka-87 and Asuka-88 meteorites, consist of various types of meteorites, such as irons, stony-irons, chondrites, achondrites and carbonaceous chondrites, including some unique specimens. The largest specimen in this collection is a 46kg LL type ordinary chondrite. departmental bulletin paper